Biodegradation of Lagoma crude oil using pig dung - Yakubu, M. Bello (African Journal of Pig Farming, 2015)
Pig dung bacteria were isolated and screened for crude oil degrading capabilities. The pig dung was also investigated for enhancement of crude oil biodegradation. Addition of chicken manure to oil polluted soil (at 10% (v/w) pollution level) stimulated the biodegradation of lagoma crude oil used in the present study. In the soil amended with pig dung, 68.2% of the crude oil was degraded, whereas only 50.7% of same oil was degraded in the unamended soil. The pH of the amended soil rose from 6.2 to 7.2. Pig dung was found to contain 1.7 x 106 cfu g-1 crude oil degrading bacteria, and 1.8 x 108 cfu g -1 aerobic heterotrophs. The crude oil utilizing bacteria were identified as species of Pseudomonas, Proteus, Klebsiella, Bacillus and Micrococcus. Pig dung could therefore be an option for crude oil pollution mitigation project.